Living Qur'an as a Model of Islamic Basic Education in the Industrial Era 4.0 - Muhammad Shaleh Assingkily (UIN Siber Syekh Nurjati Cirebon, 2019)
AbstractThe industrial era 4.0 has an impact on all aspects of life, including the aspect of education. This makes the stakeholder of education who initially puts forward cognitive aspects in the purpose of education, turns to strengthen the potentials and characters of children. One of alternatives that arises is contextualizing the Qur'an early on to the child. This article aims to study the learning activities of the tahfidh and tahsin programs applied at MI Nurul Ummah. The formulation of the problem in this research is how the living Qur'an effort at MI Nurul Ummah as a model of Islam basic education in the era of industry 4.0 is implemented. This study used a qualitative approach with two settings of activities, including the application of the tahfidh program and the tahsin al-Qur'an at MI Nurul Ummah. To get the required data relating to the focus of the research, observations, interviews, and documentation were conducted. Furthermore, data analysis is done through data reduction techniques, data presentation, and conclusions. The results of this study indicate that living qur'an efforts have been carried out at MI Nurul Ummah and can be considered as a model of basic education in the era of industry 4.0. This can be seen from the development and strengthening of children's character through concrete efforts in the form of: madrasa routines, supervisory activities, adequate time allocation, qualified educators, and intense communication with parents of students.Keywords: living Qur’an, tahfidh and tahsin, the era of industry 4.0AbstrakEra industri 4.0 berdampak kepada seluruh aspek kehidupan, tidak terkecuali aspek pendidikan. Hal ini menjadikan para pemerhati pendidikan yang semula mengedepankan aspek kognitif dalam tujuan pendidikan, beralih kepada penguatan potensi dan karakter anak. Salah satu alternatif yang muncul yakni dengan mengkontekstualisasikan al-Qur’an sejak dini kepada anak. Penelitian ini bertujuan untuk mengkaji upaya kontekstualisasi al-Qur’an melalui pembelajaran program tahfidh dan tahsin yang diterapkan di Madrasah Ibtidaiyah (MI) Nurul Ummah. Penelitian menggunakan pendekatan kualitatif dengan latar kegiatan yaitu penerapan program tahfidh dan tahsin al-Qur’an di MI Nurul Ummah. Untuk mendapatkan data yang diperlukan berkenaan dengan fokus penelitian maka dilakukan observasi, wawancara, dan dokumentasi. Selanjutnya, analisis data dilakukan melalui teknik reduksi data, penyajian data, dan simpulan. Adapun hasil penelitian ini menunjukkan bahwa upaya living qur’an telah dilaksanakan di MI Nurul Ummah dan dipandang recommended sebagai model pendidikan dasar Islam di era industri 4.0, hal ini terlihat dari pengembangan dan penguatan karakter anak melalui upaya konkrit berupa: rutinitas madrasah, kegiatan pengawasan, alokasi waktu yang memadai, tenaga pendidik yang qualified, dan komunikasi intens dengan orangtua siswa.Kata kunci: living Qur’an, tahfidh dan tahsin, era industri 4.0